THEMATIC PROGRESSION ANALYSIS IN INDONESIAN EFL STUDENTS’ THESIS ABSTRACTS - Rika Vennia Rahmawati; Eri Kurniawan (Indonesian EFL Journal, 2015)
This study examines thematic progression in thesis abstracts written by English students in Indonesia University of Education. This study employs a descriptive qualitative method since it attempts to describe and analyze textual data accurately. The data for this study come from repository.upi.edu. Five undergraduate students’ thesis abstracts were downloaded from the website published in 2014. After gathering the data, a thematic progression theory proposed by Fries (2002) is employed to analyze the data. Findings show that constant theme is the type of thematic progression that is mostly used the thesis abstracts by 52.64%. The linear theme and split rheme thematic progression pattern are also found in the abstracts. However, split rheme is found only once. Among the problems the students have probably encountered are how to write a coherent abstract and to create an appropriate logical relation among sentences in their writing. This study concludes that the students’ thesis abstracts mostly use constant theme pattern, which suggests their writing is not quite well-arranged. Since an abstract should be written in more or less 200 words and it should represent the important information of the research, students may be confused as to how to summarize their research into 200 words.Keywords: thesis abstracts, thematic progression, English students